Cytoreductive surgery with hyperthermic intraperitoneal chemotherapy for appendiceal and colorectal cancer with peritoneal carcinomatosis: Clinical outcomes at 2 tertiary referral centers in Korea. Issue 21 (May 2017) - Park, Eun Jung; Baik, Seung Hyuk; Hur, Hyuk; Min, Byung Soh; Kang, Jeonghyun; Han, Yun Dae; Cho, Min Soo; Lee, Kang Young; Kim, Nam Kyu
Abstract : Abstract: Cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC) is regarded as effective surgical treatments in patients with peritoneal metastasis. This study aimed to evaluate the clinical outcomes of CRS and HIPEC in patients with appendiceal or colorectal cancer with peritoneal carcinomatosis. A total of 66 patients who underwent CRS with HIPEC for appendiceal or colorectal cancer with peritoneal metastasis at 2 tertiary referral centers in Korea were evaluated between July 2014 and March 2016. The perioperative outcomes and postoperative complications were evaluated prospectively. The mean peritoneal cancer index (PCI) was 15.3 ± 10.5. The distributions thereof were as follows: PCI < 10, 33.3%; PCI 10–19, 36.4%; and PCI≥20, 30.3%. Regarding completeness of cytoreduction (CC), 59.1% of patients achieved CC-0, with 18.2% showing CC-1 and 22.7% showing CC-2. The mean operation time was 9.4 hours, and the mean hospital stay was 20.2 days. The overall rate of short-term complications was 74.2%; the rate of long-term complications was 10.6%. In the short-term period, most complications were grades I-II complications (62.1%), compared to grades III-V (12.1%). All long-term complications, occurring in 10.6% of patients, were grades III-V. In this study, CRS with HIPEC was deemed feasible and safe for treating stage IV appendiceal or colorectal cancer with peritoneal carcinomatosis in Koreans.